2011
DOI: 10.1111/j.1365-3121.2011.01012.x
|View full text |Cite
|
Sign up to set email alerts
|

Lithosphere density model in Italy: no hint for slab pull

Abstract: The lithosphere–asthenosphere system of the Italic region in terms of shear-velocity and density distribution with depth is suitable to investigate the geodynamic context of the region. The velocity structure is obtained through nonlinear inversion of dispersion curves compiled from surface wave tomography on cells 1° × 1° and a smoothing optimization method to choose the representative cellular model, whose layering is used as fixed (a priori) information to obtain a density model by means of linear inversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Following this procedure, it has been shown in several cases that the LVZ does not correspond to a low-density zone, and thus, it is gravitationally stable (e.g. Brandmayr et al 2011;Zhang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Following this procedure, it has been shown in several cases that the LVZ does not correspond to a low-density zone, and thus, it is gravitationally stable (e.g. Brandmayr et al 2011;Zhang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…not subject to previous basaltic melt extraction) mantle compositions. A suite of global and regional studies have shown that, as a general rule, the effects of temperature and composition on buoyancy are comparable in the shallow continental mantle (Jordan, 1975;Forte and Perry, 2000;Kaban et al, 2003;Kelly et al, 2003;Artemieva, 2007;Brandmayr et al, 2011;Tumanian et al, 2012). In the deep mantle, composition and not temperature dominates buoyancy (Trampert and van der Hilst, 2005).…”
Section: Translating the Results To Other Physical Variablesmentioning
confidence: 99%
“…Only in a few cases have formal uncertainties in tomographic results been published (e.g. Panza et al, 2007;Brandmayr et al, 2010;Cor-chete andChourak, 2010, 2011;Raykova and Panza, 2010;Gonzales et al, 2011). If uncertainties were published routinely, many seismic anomalies interpreted geologically, widely used in undergraduate teaching, and relied upon to support geochemical and geodynamic models,…”
Section: Repeatabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has been extensively applied to upper crustal problems; however, applications to the lower crust and upper mantle have been limited (e.g., Brandmayr et al 2011;Welford and Hall 2007;Welford et al 2010). Refined mesh design and sensible regularization procedures permit reasonable resolution of the Moho surface, whilst Figure 1 Tectonic map of the Tibetan Plateau (Yin and Harrison 2000).…”
Section: Structural Modeling From Seismological Tomography and Gravitmentioning
confidence: 99%